Common Drivers of Commodity Futures? - Tom L. Dudda; Tony Klein; Duc Khuong Nguyen; Thomas Walther (Queen's University Belfast, Queen's Management School, 2022)
We study potential drivers for a large cross-section of commodity futures. Unlike previous studies, we examine the effect of monthly drivers on daily returns using mixed-frequency Granger causality tests. We find real economic activity as a main driver on a monthly basis, whereas financial variables seem to affect returns at daily frequency. The linkages are time-varying for various stages of the financialization of commodity markets with an overall dissipating impact in the recent period of de-financialization. As our results strongly differ from traditional low-frequency Granger causality tests under the temporal aggregation of futures returns, we show the economic value of accessing information at a higher frequency in an out-of-sample trading study. Our findings emphasize the importance of using mixed-frequency techniques to uncover relationships between monthly-published macroeconomic variables and commodity prices.
Keywords: C58; G17; Q02; 330; Commodity futures; VAR; Granger causality; Mixed data sampling